Seed bank dynamics of the Strandveld succulent Karoo - De Villiers, Adriaan Jakobus (2013)
Please read the abstract in the section 00front of this document === Thesis (PhD (Botany))--University of Pretoria, 2007. === Plant Science === unrestricted